2007
DOI: 10.1093/bja/aem264
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane preconditioning at 1 MAC only provides limited protection in patients undergoing coronary artery bypass surgery: a randomized bi-centre trial † ‡

Abstract: This study did not show a significant preconditioning signal after 15 min of sevoflurane administration. The 15 min duration might be too short or the concentration of sevoflurane too low to induce cardioprotection detected by troponin I levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 37 publications
(37 reference statements)
1
35
0
1
Order By: Relevance
“…Several studies have addressed the potential clinical implication of cardioprotection by volatile anesthetics in patients undergoing coronary artery surgery, looking at cellular enzyme release and myocardial function (16,27,49,60). Other clinical preconditioning studies, however, have shown no significant cardioprotective effects in terms of either better preservation of myocardial function or less postoperative myocardial damage (11,48). This underscores the possibility that the clinical preconditioning protocol, patient age, and disease condition may be critical to its putative efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have addressed the potential clinical implication of cardioprotection by volatile anesthetics in patients undergoing coronary artery surgery, looking at cellular enzyme release and myocardial function (16,27,49,60). Other clinical preconditioning studies, however, have shown no significant cardioprotective effects in terms of either better preservation of myocardial function or less postoperative myocardial damage (11,48). This underscores the possibility that the clinical preconditioning protocol, patient age, and disease condition may be critical to its putative efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…We and others previously have reported, however, that older animals fail to benefit from anesthetic preconditioning (APC), ischemic preconditioning, or pharmacological preconditioning including cyclosporine A (CsA) (34,37,42,44). This could help explain the failure of preconditioning strategies to alter relevant outcomes in clinical studies (11,48). Although aging is associated with oxidative stress, which has been implicated in the pathophysiology of cardiovascular diseases, as well as cardiac injury after episodes of ischemia-reperfusion (I/R), it is still unclear whether chronic oxidative stress and the damage it causes underlies the loss of pharmacological preconditioning with aging.…”
mentioning
confidence: 99%
“…While numerous laboratory investigations have shown that anaesthetic preconditioning is an important protective mechanism in a variety of species and tissues [1][2][3][4], the results of studies performed in humans have been more equivocal. While there are several studies reporting a beneficial effect with respect to myocardial cell damage [5][6][7], myocardial function [8,9], and improved outcome [10,11], other investigators have been unable to confirm these promising findings [12][13][14][15]. In studies where the volatile anaesthetic is given continuously (i.e.…”
mentioning
confidence: 99%
“…before, during and after cardiopulmonary bypass, CPB) it is difficult to discern if the beneficial effects observed are specifically related to preconditioning, or instead partly attributable to attenuation of the reperfusion injury or 'postconditioning' [16]. In two recent studies comparing sevoflurane with propofol-based anaesthetic techniques in cardiac surgical patients, no cardioprotection was present if the volatile anaesthetic was administered for preconditioning solely before CPB [14,17]. Data from an animal experiment suggested that an interrupted administration of the volatile anaesthetic twice before CPB interspersed with a washout period confers better cardioprotection compared with a continuous administration [18].…”
mentioning
confidence: 99%
“…[2][3][4][5] Unfortunately, the clinical reproducibility and effectiveness of volatile anesthetic preconditioning have recently come into question. 6,7 Preconditioning has not translated easily to the clinical scenario and is not universally effective. Patient factors, including diabetic status 8,9 and aortic cross-clamp intervals exceeding 30 to 40 min, 10 could mitigate the effects of the preconditioning stimulus.…”
Section: Résumémentioning
confidence: 99%